2008
DOI: 10.5650/jos.57.153
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Properties and Cytotoxicity of Thermally Oxidized Oil

Abstract: Heated frying oils with different chemical properties in terms of AV (acid value), POV (peroxide value), COV (carbonyl value), and contents of polar compounds (PC) and triacylglycerol (TG), as well as color and odor, were obtained. Male Wistar rats were fed ad libitum for 12 weeks a powdered diet (AIN93G; no fat) containing 7 wt% of fresh oil (control) or one of the frying oils described above. The rats were subjected to anthropometric measurements, hematological analyses, and observations of the liver and kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 19 publications
1
30
0
1
Order By: Relevance
“…It is common understanding in Japan [11][12][13] that edible oil should have POV <30 mEq/kg for the safety reason. It has also been reported 14) that properties such as POV, COV, PC, AV, and TG have little to do with cytotoxicity causing degeneration in the liver and kidneys, but that low molecular-weight compounds…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is common understanding in Japan [11][12][13] that edible oil should have POV <30 mEq/kg for the safety reason. It has also been reported 14) that properties such as POV, COV, PC, AV, and TG have little to do with cytotoxicity causing degeneration in the liver and kidneys, but that low molecular-weight compounds…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear yet by what mechanism gluten inhibited the cytotoxicity of heated oil. We suggest that the formation of low-molecular-weight compounds causing cytotoxicity, generated through decomposition of thermally oxidized oil, was inhibited and/or decreased by gluten 14) . The difference in the effect of oils heated with amino acids and gluten on cytotoxicity was conjectured to be due to the molecular size of the melanoidin formed from them 4) .…”
Section: Diet Oilmentioning
confidence: 91%
“…Ideally, the substances should be soluble in oil and effective in very limited quantities. Soybean protein employed in the present study contained various components other than protein, but it has been confirmed 20,21) that the body weightloss promoting effects in excess of those from protein were not expected from amino acids, sucrose, and carbohydrates.Dieting oils presently marketed around the world contain Salatrim ®22) , Caprenin ®23) , Olestra ®24,25) , Econa ®26-28) and Healthy Resetta ®29-31) . Salatrim ® , Caprenin ® , and Healthy Resetta ® are triacylglycerides esterified with long and short (medium) chain fatty acids.…”
mentioning
confidence: 99%
“…Keywords: antioxidant activity; frying; polymerised triacylglycerols; prooxidant activity; tocopherols In spite of the low acute toxicity of oxidised fats and oils (Esterbauer 1993), a lot of undesirable effects were observed in some long-term tests with them (Alexander 1981;Izaki et al 1984;Kubow 1990;Esterbauer 1993;Chow 2007;Totani et. al.…”
Section: Introductionmentioning
confidence: 99%
“…The prooxidant capacity of the heated oils ranged from 58 mg to 360 mg α-tocopherol/kg and decreased in the order soybean oil > rapeseed oil > olive oil ≈ sunflower oil. It did not correlate with the content of polymerised triacylglycerols (except the sunflower oil) and was generally higher than the residual content of α-tocopherol.Keywords: antioxidant activity; frying; polymerised triacylglycerols; prooxidant activity; tocopherols In spite of the low acute toxicity of oxidised fats and oils (Esterbauer 1993), a lot of undesirable effects were observed in some long-term tests with them (Alexander 1981;Izaki et al 1984;Kubow 1990;Esterbauer 1993;Chow 2007;Totani et. al.…”
mentioning
confidence: 99%